The Effect of Picture and Picture Learning Model on Mathematics Learning Outcomes of Plane Shapes of Grade III Students of SDN 138 Palembang - Pangestu, Yayuk; Destiniar; Eka Fitri Puspa Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to see whether there is an influence of the Picture And Picture learning model on the learning outcomes of mathematics on flat shape material for grade III students of SD Negeri 138 Palembang. This study is included in the type of quantitative research that applies the Quasy Experimental Design method. It was carried out in class 3-A which consisted of 22 students and 3-B which consisted of 24 students. The instrument used was in the form of essay questions covering 5 questions. This study obtained t-test results with a significance of 0.001 <0.05 which indicates that H0 is rejected and Ha can be accepted. So it can be concluded that the implementation of the Picture And Picture learning model has a significant effect on the learning outcomes of flat shape mathematics for grade III students of SD Negeri 138 Palembang. So the Picture And Picture learning model can be an alternative in learning applied by students so that students do not feel bored when learning and to determine the effect on students' cognitive learning outcomes in maximizing the learning process